'@ SCHOOL - COMPUTER ASSISTED FOREIGN LANGUAGE EDUCATION' - THE STUDENTS' PERSPECTIVE - Ozverir, Ayse; Ozverir, Ildeniz; Arkin, Nil; Irikoglu, Musteyde (Iated-Int Assoc Technology Education A& Development, 2011)
@ School is a theme based computer assisted foreign language learning environment development project. The project is a joint project between the Eastern Mediterranean University and two secondary schools, namely Famagusta Turk Maarif College and Lefke Gazi Lycee. The project aims to improve and increase the amount of teaching and learning of foreign languages, namely English and German, in secondary schools in Northern Cyprus based on best-practices. This has been done by introducing a new teaching and learning methodology by making use of web technologies to both complement and supplement work in the classroom. The project initially targets 6th and 7th grade secondary school students and covers A1 and A2 levels of the Common European Framework Reference for Languages (CEFR) for the target languages. In respect to this, experts specializing in areas such as instructional design, curriculum development and content from the Eastern Mediterranean University worked closely with the two secondary schools to determine their needs and accordingly developed the online syllabi and content. This paper describes the elements integrated while designing the course content to cater for the needs of the learners at the two state secondary schools. The findings of the formative evaluation results which were conducted during the implementation phase of the project will also be shared.
5th International Technology, Education and Development Conference (INTED) -- MAR 07-09, 2011 -- Valencia, SPAIN
Keywords: Common European Framework of Reference for Languages (CEFR); computer assisted foreign language learning; web technologies; blended learning; online curriculum